2013
DOI: 10.5798/diclemedj.0921.2013.02.0251
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Bu çalışmanın amacı, bir üniversite hastanesinin acil yoğun bakım biriminde takip edilen çoklu travma hastalarının değerlendirilmesidir. Yöntemler: Çalışmaya Ocak 2006-Ocak 2009 tarihleri arasında fakültemizin acil yoğun bakım biriminde takip edilen çoklu travma hastaları alındı. Travma sonrası ilk altı saat içinde hayatını kaybedenler, kronik böbrek yetmezliği, kronik karaciğer hastalığı, konjestif kalp yetersizliği ve metastatik kanser hastaları çalışma dışı bırakıldı. Travmanın nedeni, yoğun bakım ve mekani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Motorized vehicle accidents are responsible for the majority of TBI-associated deaths among young adults 2,23 . Dur et al stated that mortality due to high falls and traffic accidents are the most common in trauma patients admitted to the intensive care unit; however, no statistical significance was reported 24 . Kara et al reported no association between mortality and type of trauma 20 .…”
Section: Onsdmentioning
confidence: 99%
“…Motorized vehicle accidents are responsible for the majority of TBI-associated deaths among young adults 2,23 . Dur et al stated that mortality due to high falls and traffic accidents are the most common in trauma patients admitted to the intensive care unit; however, no statistical significance was reported 24 . Kara et al reported no association between mortality and type of trauma 20 .…”
Section: Onsdmentioning
confidence: 99%
“…A study conducted in the United States reported an ICU mortality rate of 12% (26). Studies conducted in tertiary ICUs in our country have reported an ICU mortality rate ranging between 38-43% (23,24,25). Uysal et al ( 23) attributed the higher-thanexpected ICU mortality rate to the long ED wait times and the admission of patients who would not benefit from the ICU (23).…”
Section: Discussionmentioning
confidence: 98%
“…The study of Çanakçı et al (24) reported that 91.66% of patients who underwent tracheostomy died. A study by Dur et al (25) indicated that tracheostomy was performed in 6.1% of patients and 62.5% of these patients died. Our study showed that 22 (1.3%) patients underwent tracheostomy and 10 of these patients died.…”
Section: Discussionmentioning
confidence: 99%